Determinan produksi perkebunan karet di Desa Purwasari Kabupaten Bungo - Rosmeli Rosmeli; Dwi Hastuti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
Rubber plantations that used to be the mainstay of the community in Jambi Province are now being replaced by oil palm plantations, the same thing also happened in Purwasari Village, Bungo Regency. This study uses primary with respondents as many as 40 rubber farmers, from the results of the study, obtained the results together - the area of land, number of plants, age of plants, labor and fertilization costs have a significant effect on rubber production, while partially planted area and number of plants has a significant effect on rubber production, while the age of the plant, the number of laborers and the cost of fertilization have no significant effect on rubber production. Seen from the scale of production of rubber farmers in Purwasari Village are on the scale of production decreasing returns to scale.